The Potential Effect of Simvastatin on Regulatory T cells in Experimentally Induced Autoimmune Thyroiditis in Female Rats - Yaqeen Talib Mohammed; Nadia Hameed Mohammed; Inam Sameh Arif (College of Pharmacy / Mustansiriyah University, 2023)
Autoimmune thyroiditis also named Hashimoto's thyroiditis: is an inflammatory disorder of the thyroid gland. It is characterized by circulating antibodies to thyroid antigens, and enlargement of the gland with lymphocytic infiltration. Regulatory T cells (Tregs), a particular subset of CD4+ T cells that express CD25 at a markedly increased level. they can regulate immune response in order to preserve homeostasis and self-tolerance. T cell expansion and cytokine production are restricted by Tregs. The development of this autoimmune disease is influenced by TGF-ß1 shortage. Management of HT is usually a symptomatic therapy that concentrates on HT's symptoms rather than its underlying cause. Statins, the lipid lowering medications have pleotropic effects. they can alter immunological reactions. Twenty-four female rats were used for this experiment divided into four groups (n=6), the disease was induced in all groups except group1 (control) where rats only received phosphate buffer saline, group 2 (induction group), group 3 received Prednisolone 2mg\kg orally for 30 days and group 4 received Simvastatin (4mg\kg) orally for 30 days too. Hashimoto's thyroiditis was induced experimentally by subcutaneous injection of porcine thyroglobulin in Freund's adjuvant emulsion (4mg/ml). Results showed an increase in Tregs and serum TGF-ß level in rats treated with simvastatin. In conclusion, simvastatin improves the number of functioning Tregs and increases TGF-ß signaling to suppress the autoimmune reaction. Therefore, simvastatin can be a promising approach in the treatment of this disease.